Does Ad Libitum Feeding during the Peri-Partum Improve the Sow Feed Intake and Performances? - Martí, Laura (Animals (Basel), 2019)
SIMPLE SUMMARY: A strong belief characterizes the choice of the feeding curve used during the transition sow period from gestation to lactation. Stepped feeding schedules are normally applied in this period, but ad libitum fed sows may have better post-partum performance. An ad libitum feeding strategy of sows from day −5 to +5 of lactation evidenced greater voluntary feed intake than the stepped schedule from two days before to five days post-farrowing. However, ad libitum feeding during the peri-partum did not show any clear advantage on the piglet survival at farrowing or post-partum reproductive recovery of sows. ABSTRACT: This study hypothesized that the ad libitum feeding of sows during the peri-partum may increase the neonatal survival of the piglets and the post-partum recovery of the sow. The aim of the study was to evaluate the effects of two peri-partum feeding strategies (ad libitum and stepped from day 110 of gestation to day 5 post-partum) on the feed intake, the reproductive performance of sows, as well as the survival of their piglets. A total of 90 Landrace x Large-White dams sired by Duroc were used. The sows were randomly assigned to feeding treatments by balancing body condition and parity between groups. The feed intake of the sows in the peri-partum was lower in the stepped than in the ad libitum strategy. The increase of the feeding level in the ad libitum sows was not counterbalanced by higher number of weaned piglets or shorter weaned to oestrus interval.